Development and Utilization of Marine Ecological Landscape Restoration Model in Reclamation Project - MA Xuesong; TIAN Tao; WU Zhongxin; YIN Zengqiang; LIU Min; GAO Dongkui (Haiyang Kaifa yu guanli)
Driven by rapid economic advancement, there has been a notable escalation in the demand for land reclamation projects. The construction of land reclamation projects during the developmental phase inherently generates a discernible level of adversarial repercussions on the marine milieu. Hence, the environmental impact and ecological landscape reinstatement pertaining to land reclamation construction constitute indispensable concerns within this domain. This paper, through an analysis of domestic and international land reclamation projects alongside instances of ecological landscape restoration in coastal regions, presents a novel approach. This approach entails segregating regions based on longitudinal water depths and lateral geological attributes, subsequently proposing tailored restoration measures for each zone. This initiative establishes a novel marine restoration model and framework, and introduces safeguards for maritime restoration efforts. The findings of this research hold a significant import in terms of providing guidance and a point of reference for the revitalization of marine environments in reclaimed coastal areas.